PELATIHAN MANAJEMEN KEUANGAN KELUARGA BAGI KELOMPOK DASAWISMA “LELY 1” RT.08 RW.05 KELURAHAN BANDUNGREJOSARI KOTA MALANG - Tri Yulistyawati Evelina; Rena Feri Wijayanti; Ahmad Fauzi; Farida Akbarina (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
Dasawisma "LELY 1" RT 08 RW. 05 Bandungrejosari Malang, is a group of mothers of households, which is its main task as the wife is to manage all revenue/receipt of either acceptance or not of the regular routine and expenses routine or daily routine no expenditure for the purposes of his family. The problem of mothers group Dasawisma "LELY 1" the existence of the outposts are over budget so that the financial deficit occurs at the end of the month or the existence of unmet needs. The condition of the above could have been avoided if the management of the fund families done with proper planning. One of the proposed to mothers PKK is Financial management training. Problems found a) lack of understanding of the importance of family financial management, b) lack of knowledge and skills in family financial management in planning and achieving financial goals. The solutions offered are a) Increased knowledge and skills of family financial management, financial management training b) family. The fundamental contribution of the partners is a) Extension of the importance of Family financial management, b) Sharing and discussion of experience in financial management, family c family financial management Training), e) Mentoring of family financial management.